Circularity, Scepticism and Epistemic Relativism. (3rd March 2016) - Bland, Steven
Abstract : It would seem that an epistemic framework can be justified only by means of a non-circular argument that establishes its truth-conduciveness. The problem of epistemic circularity suggests that no such argument is possible. Externalists and particularists have addressed the problem of scepticism by claiming that epistemically circular arguments can establish the truth-conduciveness of a framework's epistemic methods. However, since these arguments are available for a good many frameworks, this response does nothing to answer the threat of epistemic relativism. The purpose of this paper is to offer a non-circular argument in favour of naturalistic epistemic frameworks, and therefore against epistemic relativism. The argument establishes that non-naturalistic frameworks depend on naturalistic methods for their application, and therefore, they cannot be more truth-conducive than naturalistic frameworks. This argument does not establish that naturalistic frameworks are truth-conducive, but it does provide a rational, objective reason to prefer such frameworks over their alternatives. Thus, the threats of scepticism and relativism can be answered if we deny the supposition that both challenges require a non-circular argument that establishes the truth-conduciveness of an epistemic framework.